The Cuban connection: drug trafficking, smuggling and gambling in Cuba from the 1920s to the Revolution - Sáenz Rovner, Eduardo (Latin America in translation, en traducción, em tradução, 2008)
U.S. prohibition and smuggling from Cuba -- Drug trafficking and political anarchy during the 1930s -- The Chinese and opium consumption in Cuba -- Corruption and drug trafficking in Cuba during the Second World War and the early postwar years -- Lucky Luciano in Cuba -- The Prío Socarrás government and drug trafficking -- Gambling in Cuba -- The Andean connection -- Contacts in France -- The Batista dictatorship and drug trafficking -- Revolution -- The diplomacy of drug trafficking at the beginning of the Revolution